Accumulation of amyloid‐β alters white matter integrity in cognitively unimpaired middle‐aged females. (1st February 2022) - Xia, Ying; Fazlollahi, Amir; Dore, Vincent; Bourgeat, Pierrick; Raniga, Parnesh; Martin, Nick; Salvado, Olivier; Rose, Stephen; Lupton, Michelle K.; Breakspear, Michael; Fripp, Jurgen; ,
Abstract: Background: The APOE‐ ε 4 allele is the strongest known genetic risk factor for Alzheimer's disease (AD) and is associated with higher amyloid‐β (Aβ) deposition. White matter (WM) microstructural damages are known to occur early at the preclinical stage of AD. Although stable associations between APOE‐ ε 4 status and WM alternations have been reported in patients with AD and mild cognitive impairment, few studies have described WM differences in cognitively unimpaired (CU) subjects at risk of AD. We aim to investigate associations of APOE‐ ε 4 status and Aβ load with WM microstructural changes in mid‐age CU individuals. Method: 151 CU participants from the Prospective Imaging Study of Ageing (PISA) were included (aged 44‐66, 78% female, 77 APOE‐ ε 4 carriers ( ε 4+) and 74 non‐carriers ( ε 4‐)) and underwent Aβ PET and 3T MRI scans including multi‐shell diffusion‐weighted images. Aβ load was quantified in Centiloid (CL) on PET and Aβ+ was defined as CL ≥ 20. Tract based spatial statistics (TBSS) analysis was performed on fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD) and axial diffusivity (AxD) to assess WM alternations associated with APOE‐ ε 4 status and/or Aβ load. All analyses were corrected for age and for multiple comparisons. Result: A significant effect of gender, but not APOE‐ ε 4 or Aβ status was observed on WM integrity in the full cohort. When considering females only, APOE‐ ε 4 carriers showed regional increased MD in several right WM tracts. However, these differences were no longer significant when correcting for Aβ status. In contrast, significant WM alternations associated with Aβ+ status were found when correcting for APOE‐ ε 4 status. In this female‐only subset, widespread WM microstructural damages were observed in Aβ+ ε 4+ subjects (N=10) compared to Aβ‐ ε 4+ (N=51) and Aβ‐ ε 4‐ (N=54) subjects. No significant differences were observed between Aβ‐ ε 4+ and Aβ‐ ε 4‐ subjects. Similar differences were also observed in the global diffusion metrics of WM tracts. Conclusion: These findings suggest that WM alternations associated with Aβ accumulation appear in mid‐life CU female subjects. Future studies in larger cohorts enriched for gender, APOE and Aβ status are required to clarify the relative contributions of APOE‐ ε 4 and Aβ status on WM microstructural damage.